2022
DOI: 10.1126/sciadv.abo5272
|View full text |Cite
|
Sign up to set email alerts
|

SNARE assembly enlightened by cryo-EM structures of a synaptobrevin–Munc18-1–syntaxin-1 complex

Abstract: Munc18-1 forms a template to organize assembly of the neuronal SNARE complex that triggers neurotransmitter release, binding first to a closed conformation of syntaxin-1 where its amino-terminal region interacts with the SNARE motif, and later binding to synaptobrevin. However, the mechanism of SNARE complex assembly remains unclear. Here, we report two cryo-EM structures of Munc18-1 bound to cross-linked syntaxin-1 and synaptobrevin. The structures allow visualization of how syntaxin-1 opens and reveal how pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
112
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(116 citation statements)
references
References 59 publications
4
112
0
Order By: Relevance
“…SLP has multiple binding modes during SNARE zippering. In addition to the t-SNARE complex, SLP and its adjacent regions can also recognize v-SNARE, facilitating the formation of the syntaxin-Munc18-VAMP template complex (16,22,47,(70)(71)(72). It was suggested that the physiological SNARE assemblies might start from Munc18-bound syntaxins (42,44,72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLP has multiple binding modes during SNARE zippering. In addition to the t-SNARE complex, SLP and its adjacent regions can also recognize v-SNARE, facilitating the formation of the syntaxin-Munc18-VAMP template complex (16,22,47,(70)(71)(72). It was suggested that the physiological SNARE assemblies might start from Munc18-bound syntaxins (42,44,72).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the physiological SNARE assemblies might start from Munc18-bound syntaxins (42,44,72). Then, Munc18 interacts with v-SNARE to form a syntaxin-Munc18-VAMP template complex, which may be universally conserved for Munc18-chaperoned SNARE assembly (16,(70)(71)(72). The template complex guides the formation of a partially zippered trans-SNARE complex, whereas Munc18 SLP turns to interact with the CTDs of the intermediate t-SNARE complex.…”
Section: Discussionmentioning
confidence: 99%
“…The tip of the Munc18-1 3a hairpin (a.a. 314-334) contains a loop (a.a. 314-326) that is disordered in all published Munc18-1 structures (Fig. 3A) (Misura et al, 2000;Stepien et al, 2022). The function of this loop is unclear.…”
Section: Syntaxin Linker Region Is Required To Activate the Template ...mentioning
confidence: 96%
“…In a major step toward understanding Munc18-1-chaperoned SNARE assembly, Stepien et al recently reported 3.5-3.7 Å-resolution cryo-EM structures of the synaptic template complex (Figure 1A) (Stepien et al, 2022). The structure confirms many features of the structural model derived from earlier single-molecule and structural studies: the N-terminal SNARE motifs of syntaxin-1 and VAMP2 are aligned as parallel helices, while the C-terminal halves are kept separated also in helical conformations (Baker et al, 2015; Jiao et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation